From digital disruption to dominance : leveraging fintech applications for sustainable growth - Shehadeh, Maha; Hussainey, Khaled (Technological innovation and sustainability for business competitive advantage, 2025)
The financial industry has traditionally been seen as resistant to change, but with the advent of FinTech, the landscape is shifting rapidly. FinTech applications, once merely disruptive forces, have now become dominant drivers of innovation, offering unprecedented opportunities for businesses to grow, adapt, and thrive in an increasingly digital marketplace. In an era where technology and finance intersect more than ever, From Digital Disruption to Dominance: Leveraging FinTech Applications for Sustainable Growth serves as a timely exploration into the vast world of FinTech applications and their transformative power in the business realm. Designed to serve both industry professionals and academic readers, this work offers a deep dive into the world of FinTech applications - from blockchain to digital banking, from peer-to-peer lending to robo-advisors. Readers will gain a clear understanding of how these tools not only disrupt but also offer pathways to dominance in various market segments.